(3GdWad hGdJQHjI GdeOQSjI aj GdaVGA GdCSQj hGdKbGajs - (3ajGV, efis ((3HjQhJs (3GdeQcR GdKbGaj GdYQHjs, 2004)
(3GdOcJhQI efi ajGV, QFjSI bSe Yde GdfaS aj GdLGeYI GddHfGfjI hGdCSJGPI ajg, CYOJ gPG GdcJGH aj GdCUd ef CLd GdJOQjS GdLGeYj aj GdejOGf GdJQHhj, ef CLd JZWjI eLGdGJ JQHhjI ZjQ eJhaQI HcKQI aj GddZI GdYQHjI, hdPdc fLO ajg aUhdkG HMKjI eKd GdYfa Ch GdcheHjhJQ Ch GdeTGcd GdJQHhjI aj GdeOGQS(B... (3ceG fLO aUhdkG eJQLeI Yf (B"(3GdJMdjd GdfaSj ddeOQSI ceDSSI(B" (3Ch (B"(3GdMjGI GdeOQSjI hONhd GdWad Edi GdeOQSI(B". (3Ef JYeje GdeOQSI ceDSSI aj GdYGde GdMOjK LYd ef GdJQHjI egfI eQcRjI aj Ohd GdYGde GdeJbOe, hHOQLI Cbd aj GdYGde GdKGdK GdPj ffJej Edjg(B. (3hgj JWeM Edi JQHjI GdWad hLYdg MQkG(B! (3hGdJMOj GdCcHQ GdPj JWQMg GdJQHjI YqHQ Yfg cGfW Hbhdg (B"(3cja jecf GdLeY Hjf GdNVhY ddVZW eY ehgHI GdGMJaGX HGdMQjI?(B". (3hdbO JMhdJ GdeOQSI efP fgGjI GdbQf GdJGSY YTQ Edi eQcR CSGSj ddJYHjQ Yf gPg GdegeI GdeSJMjdI GdJj JgOa Edi EfJGL GdeLJeY Yf WQjb JYdje GdehGWfjf(B. (3hef gfG VQhQI GdbjGe HYed cHjQ Ydi UYjO GdJQHjI aj GdYGde GdYQHj(B. (3aCcKQ CfXeJfG aTdkG gh fXGefG GdJQHhj GdPj SeM HhLhO (B70 (3edjhf Ceqj aj HOGjI GdCdajI GdKGdKI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Children; Enfants; Etablissement scolaire et parents; Milieu Socio-Culturel; School and Parents Socio-Cultural Milieu; (3GdCWaGds; (3GdeOQSI hGdCgd GdhSW GdKbGaj GdGLJeGYjs